Skin whitening effect of brewer's spent yeast extract - ZHANG Jun, HAN Wenlong, JIN Mengjia, ZHANG Renping, LI Qianwei, ZHANG Yunshu, LIU Jiale, XIONG Jiangshan, WANG Chen (Zhongguo niangzao)
In order to explore the feasibility of brewer's spent yeast (BSY) extract as whitening factor of skincare cosmetics. BSY extract was extracted by ethanol solution, and using extraction ratio as evaluation index, the extraction conditions were optimized by single factor tests and response surface tests. The four extracts of different polarity were obtained from BSY extract by ethanol, petroleum ether, ethyl acetate and n-butanol, respectively. Using anti-ultraviolet, anti-oxidation and tyrosinase inhibition activities as evaluation indexes, the effect of four different polar extracts on whitening effect was investigated. The results showed that under the conditions of solid-liquid ratio 1∶28 (g∶ml), ethanol volume fraction 79%, extraction temperature and time were 57 ℃ and 1.5 h, the actual extraction yield of BSY was the highest of 38.1%. Different polarities solvents extracts had absorption effects on ultraviolet radiation, and the UV absorption rate of petroleum ether extract was the highest (>87%). The ABTS free radical scavenging rate was the highest in ethanol extract (96.49%). The free radical scavenging rate of DPPH was the highest in ethyl acetate extract (93.49%). Extracts from different polar solvents exhibited tyrosinase inhibition, with petroleum ether extract showed the highest inhibition at 33.29%. The results of this study could provide guidance for the application of BSY extract in skincare cosmetics, and could be used in the development of whitening skincare products.